Purpose in Management Research: Navigating a Complex and Fragmented Area of Study - Chua, Nathania; Miska, Christof; Mair, Johanna; Stahl, Günter K. (Academy of Management Annals, 2024)
Management research on “purpose” is dispersed. This is because scholars apply different perspectives on purpose, each associated with distinct approaches to its study. We find that one perspective views purpose as embedded in the business–society context or as embodied within organizations. A second perspective looks at the purpose of the organization and its purpose to specific stakeholders. We reviewed management literature on purpose conducted over the past two decades to unearth this fragmentation further and uncover possibilities for integration. We identify four themes that anchor the disjointed literature: identity, performance, objectives, and change. In addition, we organize the literature across six dimensions of purpose as a concept. Each dimension surfaces existing dichotomies in research: property, scope, stability, materiality, motive, and rationality. Both the anchoring themes and conceptual dimensions establish the groundwork for a programmatic agenda for future research, aimed to support purpose research as a distinct area of study in management.